Avaliação da entomofauna em frutos de espécies florestais do cerrado - Silva Junior, Josamar Gomes da (2016)
Studies of forest insect fauna are important parts because it forms the first stage of integrated pest management, which seeks to increase and preserve the natural mortality factors, through the possible use of integrated control techniques informed in ecological and economic parameters. The surveys provide information about the biological cycle, spiking, population density of insects among others. Constant monitoring allows the proper conduct of a pest management program, reducing control costs, increase efficiency and without harming the performance of forests and reduce insecticide applications and reducing environmental contamination. The research aimed to identify the species of insect predators of fruits and seeds of tree species of Savannah. Within six months, the study was conducted at Cavalo Branco I Farm, in the municipatility of Nossa Senhora do Livramento, State of Mato Groso, Brazil. The emerged adult insects fruits were identified and their valued damages. Samples were collected every two weeks in pre and post drop seeds and fruits in the sample area within the boundaries of the property and the region. Infestation rates (ti %) were evaluated by multivariate cluster analysis species. We identifed the species: Lasioderma serricorne (Fabricius, 1792), Hypothenemus seriatus (Eichhoff, 1872), Eubulus sp, Heterotermes longiceps (Snyder, 1924), Anastrepha obliqua (Macquart, 1835), Taeniaptera lasciva, (Fabricius, 1798), Pachymerus sp., Dufauxia guaicurana (Lane, 1955), Gibbobruchus cavillator (Fåhraeus, 1839) and Amblycerus sp., totaling 399 emerged insects.